(untitled) (Bangladesh Journal of Microbiology, 2019)
This study was undertaken to find out the presence of contaminating microorganisms in commonly available Syzygium aromaticum samples collected from different areas of Bangladesh and also to evaluate the antibacterial traits of these Syzygium aromaticum samples against food born pathogens. Total viable bacterial count (TVBC) was determined on nutrient agar and for the isolation of specific microorganisms different selective media were used. Crude, ethanol, methanol, hot water and cold water extracts of the samples were prepared for analysing their antibacterial activity using the agar well diffusion method. Furthermore, the minimum inhibitory concentration (MIC) of the crude extracts was determined. TVBC was found between 104 to 106 cfu/g. None of these samples showed the presence of fungus. Staphylococcus spp. was present almost in all the samples between 104 to 106 cfu/g while Bacillus spp. was noticed only in one sample. In vitro antibacterial activity of the crude, methanolic and ethanolic extracts of the samples was found to be effective mostly against Escherichia coli, Klebsiella spp., Listeria spp., Pseudomonas spp. and Bacillus spp. On the contrary, hot water extracts of only two samples showed antibacterial property against Pseudomonas spp., Listeria spp. and Klebsiella spp. MIC was confirmed by using 96 well plate methods and the minimum inhibitory concentration was between 11.75 to 94 mg/ml. Bangladesh J Microbiol, Volume 35 Number 1 June 2018, pp 1-5